A review of the transverse modules of the formative cycles of vocational studies - Solsona Solé, Joan (Avances en Supervisión Educativa, 2015)
The objective of this article is to describe the confrontation of two curricular models differentiated of the modules of Training and Employment Guidance and Bussiness and Entrepreneurship, which are part of the training courses of vocational studies. On the one hand, there is the homogeneous model without differentiating the professional levels; on the other hand, there is the progressive model which does take into account the professional level with differentiated competences.On observing the educational centres which provide higher vocational training courses it is noted that there is a high number of students who do not participate in lifelong learning in a very important aspect of their lives as employability and entrepeneurship as they have the transversal modules of Training and Employment Guidance and Bussiness and Entrepreneurship validated. Therefore, it is proposed to implement a progressive curricular model of the before mentioned modules in the middle and higher vocational training courses, detailing and differentiating the respective professional profiles.
Keywords: vocational studies; transverse modules; professional skills